A Dynamic Model for Sustainable Tourism Village Planning Based on Local Institutions - Widhianthini Widhianthini (The Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Abstract. Regional development involves optimizing the utilization of the region's resources in an integrated and harmonious way. This regional development is realized through a comprehensive approach that includes physical, economic, social, cultural, and environmental aspects. The integration of these aspects will lead to sustainable development in the region. However, development is currently often looked at only from a physical way so that the concept of sustainability only exists on paper and does not involve local institutions in the region, such as in the tourism village development program. The purpose of this study is to analyze the relationship between physical/environmental, economic, and social aspects and local institutions in Tabanan Regency, Bali Province in realizing sustainable tourism villages. Primary and secondary data were combined through questionnaires and interviews. This study uses dynamic system analysis. Including all three aspects results in a new model of system dynamics and it can show that the local institutional aspect is an aspect that must be taken into account in designing a model of sustainable development in a region or area. This is so that problems that arise can be eliminated as early as possible and alternative policies can be obtained that should be adopted by policy makers, strengthened by local rules (awig-awig) and local government laws.Keywords. Regional development, local institutions, sustainable tourism villages, dynamic system, awig-awig.Abstrak. Pengembangan wilayah merupakan optimasi pemanfaatan sumberdaya yang dimiliki suatu wilayah secara terpadu dan serasi. Pengembangan wilayah ini diwujudkan melalui pendekatan yang bersifat komprehensif mencakup aspek fisik, ekonomi, sosial, budaya, dan lingkungan. Keterpaduan aspek ini akan mengarah pada pembangunan berkelanjutan di suatu wilayah. Namun, ukuran pembangunan saat ini sering dilihat secara fisik saja sehingga konsep berkelanjutan hanya sebatas di atas kertas saja dan tidak melibatkan kelembagaan lokal di suatu kawasan, seperti pada program pengembangan kawasan desa wisata. Tujuan penelitian ini adalah untuk menganalisis keterkaitan aspek-aspek fisik/lingkungan, ekonomi, sosial dengan kelembagaan lokal di Kabupaten Tabanan, Propinsi Bali dalam mewujudkan kawasan desa wisata yang berkelanjutan. Data primer dan sekunder dikombinasikan melalui kuesioner dan wawancara. Penelitian ini dianalisis dengan sistem dinamik. Dengan memasukkan ketiga aspek tersebut maka akan didapatkan model baru dalam sistem dinamik dan dapat terlihat bahwa aspek kelembagaan lokal merupakan aspek yang harus diperhitungkan dalam pembuatan model pembangunan berkelanjutan di suatu wilayah atau kawasan sehingga permasalahan-permasalahan yang timbul dapat dieliminir sedini mungkin dan diperoleh alternatif-alternatif kebijakan yang harus diambil oleh para pengambil kebijakan untuk masing-masing daerah yang diperkuat dengan aturan-aturan lokal (awig-awig) dan aturan pemerintah daerah.Kata kunci. Pengembangan wilayah, kelembagaan lokal, kawasan desa wisata berkelanjutan, sistem dinamik, awig-awig.